Optimization of exposure parameters in automatic optimization of exposure parameters (Aop) mode of full field digital mammography (FFDM) system: breast phantom study / Hairenanorashikin Sharip and Rafidah Supar - Sharip, Hairenanorashikin; Supar, Rafidah (Universiti Teknologi MARA, Negeri Sembilan, 2020)
This experimental study investigated the significant different in image quality and dose between different automatic exposure of exposure parameter (AOP) mode in full field digital mammography (FFDM) system. CIRS012A and PMMA breast phantom (4cm, 5cm and 6 cm thickness) were used as subject using Senographe Essential FFDM system. TLD chip was used as dose measurement tool. Exposures were taken in cranio-caudal projection. 2 radiographers with more than 10 years of working experience in performing mammography scored the image independently. Kappa finds a good agreement between raters (kappa value=0.9, p<0.01). One-way ANOVA shows a significant different in dose between CNT and DOSE mode (p=0.013). However, there is no significant different in image quality between CNT, DOSE and STD (p>0.05). DOSE mode is the preferred selection in optimizing between dose and image quality.